The Effect of Mangrove Crab Shell Powder (Scylla serrata) Addition on the Iron Content of Cookies - Anggraeni, Ni Kadek Ayu Rina; Widnyani, Ida Ayu Putu Ary; Rabani RS, I Gusti Agung Yogi; Sintyadewi, Putu Rima; Putra, Anak Agung Ngurah Dwi Ariesta Wijaya (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Increased awareness of healthy lifestyles has spurred the growth of functional food trends among communities. Iron deficiency causes anemia, a major nutritional problem in Indonesia. Mangrove crab shells are a local source of iron. In most cases, the edible portion of crabs is limited to the meat, while the shells are discarded, leading to their high potential as a source of waste. The purpose of this study was to determine the effect of adding mangrove crab shell powder on the iron content of cookies. This study employed an experimental design using a Complete Randomized Design (CRD), with treatments of adding different concentrations of mangrove crab shell powder (0%, 3%, 6%, 9%, 12%, 15%). The data were analyzed using ANOVA and Duncan’s multiple range test. Findings indicated that adding mangrove crab shell powder significantly affected the iron content of the cookies. The iron content of the modified cookies ranged from 64.13 to 187.54 mg. The higher the concentration of crab shell flour added, the higher the iron content of the cookies. It is recommended that further research be conducted, encompassing organoleptic evaluation, microbiological contamination analysis, and heavy metal contamination assessment, to ensure the product's safety and quality. It is hoped that this research can serve as a reference on the use of crab shell waste as a source of iron that is beneficial to health.